Dopaminergic modulation of phase reversal in desert locusts - Alessi, Ahmad M.; O'Connor, Vincent; Aonuma, Hitoshi; Newland, Philip L. (Frontiers in Behavioral Neuroscience, 2014)
Phenotypic plasticity allows animals to modify their behaviour, physiology and morphology to adapt to environmental change. The global pest, the desert locust, shows two extreme phenotypes; a solitarious phase that is relatively harmless and a gregarious phase that forms swarms and causes extensive agricultural and economic damage. In the field, environmental conditions can drive isolated animals into crowded populations and previous studies have identified the biogenic amine serotonin as a key determinant of this transition. Here we take an integrated approach to investigate the neurochemical, physiological and behavioural correlates defined by a laboratory based paradigm that mimics facets of swarm break down as gregarious locusts become isolated. Following isolation there was an increased propensity of locusts to avoid conspecifics, and show a reduced locomotion. Changes in choice behavior occurred within 1hr of isolation although isolation-related changes progressed with increased isolation time. Isolation was accompanied by changes in the levels of the biogenic amines dopamine, octopamine and serotonin within the CNS within 1hr. Dopamine levels were higher in isolated animals and focused on the role played by this transmitter in synaptic changes that may underpin solitarization. Dopamine reduced synaptic efficacy at a key central synapse between campaniform sensilla and a fast extensor tibiae motor neuron that is involved in limb movement. We also show that dopamine injection into the haemocoel was sufficient to induce solitarious-like behaviour in otherwise gregarious locusts. Further, injection of a dopamine antagonist, fluphenazine, into isolated locusts induced gregarious-like behaviour. This highlights that dopaminergic modulation plays an important role in the plasticity underpinning phase transition and sets a context to deepen the understanding of the complementary role that distinct neuromodulatory play in polyphenism in locusts.